Detailed study on the thermal, photo-physical and electrochemical properties and OFET applications of D-pi-A-pi-D structured unsymmetrical diketopyrrolopyrrole materials - Bharath, D.; Chithiravel, Sundaresan; Sasikumar, M.; Chereddy, Narendra Reddy; Shanigaram, Balaiah; Bhanuprakash, K.; Krishnamoorthy, K.; Rao, V. Jayathirtha (RSC Advances, 2015)
A series of seven unsymmetrical diketopyrrolopyrrole (DPP) derivatives with donor-pi-acceptor-pi-donor (D-pi-A-pi-D) architecture have been designed, synthesized and well characterised. The effect of the electron donating capacity and extent of electronic conjugation of the end-capping units on the thermal, photo-physical and electrochemical properties of the synthesized materials was thoroughly investigated using various experimental techniques and theoretical calculations. Organic field-effect transistors (OFETs) were fabricated using these materials to obtain their hole/electron transporting characteristics. All these materials showed moderate to good hole transporting ability, and the OFET fabricated using the DPP-derivative with benzofuran and pyrene end groups exhibited a hole mobility of 6.7 x 10(-4) cm(2) V-1 s(-1) with VT of similar to 9 V. The observed photo-physical, electrochemical, thermal, and charge carrier properties of the synthesized DPP-derivatives indicated their applicability in various areas like organic photovoltaics, disposable electronics and biomedical devices.

Role of acceptor strength on OFET properties of small molecular organic semiconducting materials with D-A-D architecture - Sasikumar, M.; Bharath, D.; Kumar, G. Siva; Chereddy, Narendra Reddy; Chithiravel, S.; Krishnamoorthy, K.; Shanigaram, Balaiah; Bhanuprakash, K.; Rao, V. Jayathirtha (Synthetic Metals, 2016)
Two organic semiconducting materials 2,5-didodecyl-3,6-bis(4-(11-dodecyl-11H-benzo[a]carbazol-8yl)phenyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione. (BCDPP) and 1,5-didodecyl-3,7-bis(4-(11-dodecyl-11H-benzo[a]carbazol-8-yl)phenyl)dipyrrolo[3,2-b:3',2'-e]pyrazine-2,6(1H,5H)-dione (BCPzDP) with D-A-D architecture have been designed, synthesized and well characterized. Both the materials have benzocarbazole donor end-capping units. While BCDPP contains well explored diketopyrrolopyrrole (DPP), BCPzDP possesses electron deficient dipyrrolopyrazinedione (PzDP) as acceptor moiety. The importance of the nature of acceptor moiety in tuning the charge transport properties of the synthesized materials is explored. Thermal, photo-physical and electrochemical properties of these materials are measured and solution processed OFETs are fabricated. OFETs with BCDPP show unipolar p-type semiconducting properties with hole mobility of 1.02 x 10(-4) cm(2) V-1 s(-1) and OFETs of BCPzDP exhibit ambipolar charge transport behaviour with optimal saturation hole and electron mobilities of 0.0054 and 0.0013 cm(2) V-1 s(-1), respectively. (C) 2016 Elsevier B.V. All rights reserved.